Analysis of Internet Utilization for the Community in Terms of Rural and Urban Conditions in the Province of Indonesia - Suhardjono S; Pandu Adi Cakranegara; Ade Risna Sari; Rudy Max Damara Gugat; Nanny Mayasari (Institute of Computer Science (IOCS), 2022)
The advancement of information and communication technology necessitates the establishment of internet telecommunications networks to serve all regions of Indonesia. The necessity for internet connection has evolved into a pattern of community requirements toward a technologically savvy and digital society. The government of Indonesia has carried out equitable distribution of internet networks in order to assist the efforts of the 4.0 technology era. The purpose of this research is to examine how Indonesians use the internet, particularly in rural and urban locations across the country. The data visualizations are used in the analysis for each province in Indonesia to determine the purpose of internet use in the community. by understanding the purpose of internet use in rural and urban populations across all provinces in Indonesia in order to acquire statistics on telecommunications development and the most prevalent use that is useful in people's daily lives The data is based on Central Statistics Agency data on internet use in rural and urban areas throughout 34 Indonesian provinces. According to the findings, the most common reasons for people in Indonesia to use the internet are for social media purposes, for information and news, and for entertainment.